2017
DOI: 10.1038/onc.2017.383
|View full text |Cite
|
Sign up to set email alerts
|

DHRS2 inhibits cell growth and motility in esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is highly prevailing in Asia and it is ranked in the most aggressive squamous cell carcinomas. High-frequency loss of heterozygosity occurred in chromosome 14q11.2 in many tumors including ESCC, suggesting that one or more tumor-suppressor genes might exist within this region. In this study, we identified the tumor-suppressing role of DHRS2 (short-chain dehydrogenase/reductase family, member 2) at 14q11.2 in ESCCs. Downregulation of DHRS2 occurred in 30.8% of primary E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 37 publications
2
27
4
Order By: Relevance
“…HEP27 protein interacts with MDM2, which is a negative regulator of p53, resulting in p53 stabilization and induction of p53 transcriptional target genes (46). More recently, downregulation of DHRS2 was reported in ESCC tissues and its downregulation was associated with ESCC aggressiveness and clinical staging (47). Thus, that report arrived at the opposite conclusions from those in our study.…”
Section: Discussioncontrasting
confidence: 96%
“…HEP27 protein interacts with MDM2, which is a negative regulator of p53, resulting in p53 stabilization and induction of p53 transcriptional target genes (46). More recently, downregulation of DHRS2 was reported in ESCC tissues and its downregulation was associated with ESCC aggressiveness and clinical staging (47). Thus, that report arrived at the opposite conclusions from those in our study.…”
Section: Discussioncontrasting
confidence: 96%
“…4B and C). DHRS2 is reported to stabilize p53 levels via Ser15 phosphorylation in esophageal squamous-cell carcinoma cells (Zhou et al, 2018). However, we observed no changes in p53…”
Section: Internal Synthesis Of Polyp Leads To Downregulation Of the Dcontrasting
confidence: 78%
“…One such example is DHRS2, which showed drastic changes in mRNA levels and was completely undetected in all five Ppk1 biological replicates. DHRS2 protein downregulation via shRNA was previously shown to decrease p53 phosphorylation at Ser15 (Zhou et al, 2018). We observed no significant change in phosphorylated p53 (Ser15) levels accompanying polyP-induced DHRS2 downregulation.…”
Section: Discussioncontrasting
confidence: 59%
“…Moreover, double homeobox A pseudogene 10, located in chr14q11.2, promotes an aggressive phenotype by binding lysine-specific histone demethylase 1 and repressing large tumor suppressor kinase 2 and Ras-related glycolysis inhibitor and calcium channel regulator expression levels in NSCLC (17). Furthermore, previous studies have revealed that chr14q11.2 may participate in cancer development (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%